THE INFLUENCE OF LEADERSHIP, WORK MOTIVATION AND EMPLOYEE ENGAGEMENT ON EMPLOYEE PERFORMANCE AT THE REGIONAL INSPECTORATE OF SOUTHEAST SULAWESI PROVINCE - Wahyuni, Nita; Muthalib, Abdul Azis; Supriadin, Nofal (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Leadership, work motivation, and employee engagement are key factors influencing organizational productivity and effectiveness, including in the public sector. However, in the Regional Inspectorate of Southeast Sulawesi Province, structural challenges and resource limitations often hinder the optimal performance of employees, highlighting the importance of analyzing these three variables. This study identifies a knowledge gap concerning the relationship between leadership, work motivation, and employee engagement and their impact on employee performance in a complex public sector environment. The research methodology employed a quantitative approach through questionnaire surveys administered to 48 employees in the Regional Inspectorate of Southeast Sulawesi Province to examine the significant effects of these variables on employee performance. The study's findings reveal that leadership, work motivation, and employee engagement significantly influence performance, with work motivation emerging as the dominant variable, thus providing a basis for more effective human resource development strategies in the public sector.